The Current State of Plastic Surgery Residency Wellness Programs: Benefits and Barriers - James E. Fanning, BS; Ashit Patel, MB ChB; Jeffrey E. Janis, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Wellness programs are especially important in residency. However, the resources available to plastic surgery residents through residency wellness programs have not been described. This study reports current plastic surgery residency wellness programs’ organization, leadership, and resources. Methods:. An anonymous and voluntary e-mail survey was sent to 106 plastic surgery residency program directors through May and June 2022. Features of residency wellness programs were detailed, and program directors’ sentiments towards residency wellness programs were evaluated. Results:. A 30.2% (32 of 106) complete response rate was achieved. Nearly 90% (87.5%, 28 of 32) of program directors indicated the presence of a wellness program. More than 75% (21 of 28) of programs are supported by the Office of Graduate Medical Education. Wellness events were offered by 92.9% (26 of 28) of programs. More than half of programs offered resources for mental health, physical health, mentorship, and protected time. Several resources were associated with the presence of wellness leadership roles, suggesting residents can positively shape wellness program offerings. Program directors strongly indicated that wellness programs are important, relevant, and effective. Additionally, 75% (24 of 32) report a desire to learn about wellness programs at other plastic surgery residency programs. Conclusions:. Resources offered through plastic surgery residency wellness programs are comparable to those in other specialties. However, plastic surgery programs vary in the resources offered to residents and barriers to access exist. Greater involvement of residents in plastic surgery wellness programs may better support physician wellness.